2012
DOI: 10.1073/pnas.1202906109
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-inflammatory lipoxin A 4 is an endogenous allosteric enhancer of CB 1 cannabinoid receptor

Abstract: Allosteric modulation of G-protein–coupled receptors represents a key goal of current pharmacology. In particular, endogenous allosteric modulators might represent important targets of interventions aimed at maximizing therapeutic efficacy and reducing side effects of drugs. Here we show that the anti-inflammatory lipid lipoxin A 4 is an endogenous allosteric enhancer of the CB 1 cannabinoid receptor. Lipoxin A 4 was detected in brain tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
198
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(210 citation statements)
references
References 52 publications
9
198
1
Order By: Relevance
“…We next performed functional interaction studies between each putative modulator and the cannabinoids previously shown to be modulated by either pregnenolone or lipoxin A4. In contrast to studies reporting attenuation of D 9 -THCinduced activation of pERK1/2 by pregnenolone in CHO-hCB 1 cells (Vallee et al, 2014), and enhancement of anandamidemediated inhibition of cAMP formation by lipoxin A4 in HEK-CB 1 cells (Pamplona et al, 2012), our results revealed a complete lack of modulation of CB 1 R signaling by these compounds at concentrations up to 10 mM and 500 nM, respectively (Fig. 5).…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…We next performed functional interaction studies between each putative modulator and the cannabinoids previously shown to be modulated by either pregnenolone or lipoxin A4. In contrast to studies reporting attenuation of D 9 -THCinduced activation of pERK1/2 by pregnenolone in CHO-hCB 1 cells (Vallee et al, 2014), and enhancement of anandamidemediated inhibition of cAMP formation by lipoxin A4 in HEK-CB 1 cells (Pamplona et al, 2012), our results revealed a complete lack of modulation of CB 1 R signaling by these compounds at concentrations up to 10 mM and 500 nM, respectively (Fig. 5).…”
contrasting
confidence: 55%
“…These latter compounds are particularly intriguing because they potentiate agonist binding to the CB 1 R, at the same time inhibiting agonist activity in numerous functional assays (Price et al, 2005;Horswill et al, 2007). Other endogenous ligands, including pregnenolone, pepcans, and lipoxin A4, may also act allosterically at CB 1 Rs, as was recently suggested (Bauer et al, 2012;Pamplona et al, 2012;Vallee et al, 2014). However, further studies are required to validate these putative allosteric effects.…”
mentioning
confidence: 96%
“…Blockade of AEA uptake by UCM707 abolished hyperkinesia in rodent models of HD and reduced spasticity in MS rats [178]. However, the elevation in AEA could produce psychotropic effects and tolerance upon CB 1 R activation [179], which has not been seen as a side effect of CBD [180]. Therefore, the binding of CBD to the AEA transporter will not provide a therapeutic effect in movement disorders.…”
Section: Cbd Transporter Targets In Movement Disordersmentioning
confidence: 99%
“…This new class of molecules includes the anti-inflammatory lipid lipoxin A4, which, by enhancing AEA-induced CB1 activation, displays a protective effect against ␤-amyloid (1-40)-induced spatial memory impairment in mice (653). Negative modulators are the ␣-hemoglobin-derived small peptide endocannabinoids (or pepcans), and the neurosteroid pregnenolone (51, 867).…”
Section: Endogenous Allosteric Modulators Of Cb1 Receptorsmentioning
confidence: 99%